Clinical approach to the patient in critical state following immunotherapy and/or stem cell transplantation: Guideline for the on-call physician - Constantinescu, Catalin; Bodolea, Constantin; Pasca, Sergiu; Teodorescu, Patric; Dima, Delia; Rus, Ioana; Tat, Tiberiu; Achimas-Cadariu, Patriciu; Tanase, Alina; Tomuleasa, Ciprian; Einsele, Hermann (Journal of Clinical Medicine, 2019)
The initial management of the hematology patient in a critical state is crucial and poses a great challenge both for the hematologist and the intensive care unit (ICU) physician. After years of clinical practice, there is still a delay in the proper recognition and treatment of critical situations, which leads to late admission to the ICU. There is a much-needed systematic ABC (Airway, Breathing, Circulation) approach for the patients being treated on the wards as well as in the high dependency units because the underlying hematological disorder, as well as disease-related complications, have an increasing frequency. Focusing on score-based decision-making on the wards (Modified Early Warning Score (MEWS), together with Quick Sofa score), active sepsis screening with inflammation markers (C-reactive protein, procalcitonin, and presepsin), and assessment of microcirculation, organ perfusion, and oxygen supply by using paraclinical parameters from the ICU setting (lactate, central venous oxygen saturation (ScVO2), and venous-to-arterial carbon dioxide difference), hematologists can manage the immediate critical patient and improve the overall outcome.
CRIS-Team Scopus Importer:2023-03-23
Keywords: ABCDE approach; Cytokine release syndrome; Hematology patient; MEWS-based clinical approach; Sepsis screening